2020
DOI: 10.1063/5.0008688
|View full text |Cite
|
Sign up to set email alerts
|

Exciton localization in tubular molecular aggregates: Size effects and optical response

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 74 publications
3
28
0
Order By: Relevance
“…A more quantitative analysis revealed that for all nanotubes considered, the spectrum could be interpreted in terms of two dominant optical transitions with mutually perpendicular transition dipoles. This is consistent with having highly delocalized exciton states in tubular aggregates, 37,38 which have optical selection rules such that there is one super-radiant exciton transition with its transition dipole along the tube's axis and two degenerate ones (usually higher in energy than the first transition) with their transition dipoles perpendicular to the axis. 65 The experiments were further analyzed in terms of a Frenkel exciton model, which revealed that small variations in the molecular orientations between different aggregates could explain the differences in their respective polarization resolved spectra.…”
Section: Experimental Correlation Of Linewidthssupporting
confidence: 69%
See 2 more Smart Citations
“…A more quantitative analysis revealed that for all nanotubes considered, the spectrum could be interpreted in terms of two dominant optical transitions with mutually perpendicular transition dipoles. This is consistent with having highly delocalized exciton states in tubular aggregates, 37,38 which have optical selection rules such that there is one super-radiant exciton transition with its transition dipole along the tube's axis and two degenerate ones (usually higher in energy than the first transition) with their transition dipoles perpendicular to the axis. 65 The experiments were further analyzed in terms of a Frenkel exciton model, which revealed that small variations in the molecular orientations between different aggregates could explain the differences in their respective polarization resolved spectra.…”
Section: Experimental Correlation Of Linewidthssupporting
confidence: 69%
“…This is the most commonly considered type of disorder, responsible for exciton localization, a rather weak effect in tubular aggregates. 37,38 In ensemble spectra, such disorder leads to line broadening, which to some extent is mitigated by exchange narrowing. 3,25 While probably this type of disorder also plays a role in ZnChl nanotubes, it does not lead to a natural explanation of the linewidth anomaly.…”
Section: B Sources Of Intra-aggregate Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…We note that the notion of a particular symmetry in the exciton states is approximately valid even in the presence of disorder as long as the exciton delocalization length is at least on the order of the tube’s circumference. 48 For tubular nanotubes, exciton localization by disorder is suppressed due the locally two-dimensional nature of the tube and the long-range dipole–dipole interactions 32 , 49 implying that the approximate symmetries and optical selection rules indeed often persist under experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…This in turn is a consequence of the strong intermolecular excitation transfer interactions and the fact that tubular aggregates are not truly one-dimensional systems, leading to weak exciton localization. 32 , 49 …”
Section: Resultsmentioning
confidence: 99%